Risk of future stroke in patients with a diagnosis of peripheral vertigo in the emergency department - Choi, Jeong‐Yoon; Kim, Seok; Boo, Dachung; Yoo, Sooyoung; Kim, Hyo‐Jung; Kim, Jun Yup; Lee, Keon‐Joo; Kang, Jihoon; Kim, Beom Joon; Han, Moon‐Ku; Bae, Hee‐Joon; Kim, Ji‐Soo (European journal of neurology, 2023)
Background and purpose The temporal characteristics of stroke risks were evaluated in emergency department patients who had a diagnosis of peripheral vertigo. It was also attempted to reveal the stroke risk factor amongst those with peripheral vertigo. Methods This is a parallel‐group cohort study in a tertiary referral hospital. After assigning each of 4367 matched patients to the comparative set of peripheral vertigo and appendicitis‐ureterolithiasis groups and each of 4911 matched patients to the comparative set of peripheral vertigo and ischaemic stroke groups, the relative stroke risk was evaluated. In addition, to predict the individual stroke risk in patients with peripheral vertigo, any association between the demographic factors and stroke events was evaluated in the peripheral vertigo group. Results The peripheral vertigo group had a higher stroke risk than the appendicitis‐ureterolithiasis group (hazard ratio 1.73, 95% confidence interval 1.18–2.55) but a lower risk than the ischaemic stroke group (hazard ratio 0.30, 95% confidence interval 0.24–0.37). The stroke risk of the peripheral vertigo group was just below that of small vessel stroke. The stroke risk of the peripheral vertigo group differed markedly by time: higher within 7 days, moderate between 7 days and 1 year, and diminished thereafter. Old age (>65 years), male gender and diabetes mellitus were the risk factors for stroke in the peripheral vertigo group. Conclusion Patients with a diagnosis of peripheral vertigo in the emergency department showed a moderate future stroke risk and so a stroke preventive strategy tailored to the timing of symptom onset and individual risk is required. Patients with a diagnosis of peripheral vertigo in the emergency department showed a moderate future stroke risk, distinct from other nonvascular medical conditions. The risk was higher within 7 days and moderate between 7 days and 1 year; old age (>65 years), male gender and diabetes mellitus appeared to be stroke risk factors. The results highlight a stroke preventive strategy tailored to the timing of symptom onset and individual risk for peripheral vertigo patients in the emergency department.